Effect of La3+ substitution on the structural and magnetic properties of Mn-Zn ferrite prepared by sol-gel auto-combustion method - Guan, B.H. (Trans Tech Publications Ltd, 2018)
Spinel ferrite with the chemical formula of Mn0.5Zn0.5LaxFe2-xO4 (x = 0.02, 0.04, 0.06, 0.08, 0.10) were prepared by a sol-gel auto-combustion method. The effect of the rare-earth substitution on the microstructural properties of the synthesized powders were investigated through X-ray diffraction (XRD) and field-emission scanning electron microscopy (FESEM), while for the magnetic properties, vibrating sample magnetometer (VSM) measurements were made. XRD patterns revealed characteristic peaks corresponding to spinel Mn-Zn ferrite structures with accompanying secondary phases, such as Fe2O3 and LaFeO3. The initial addition of La3+ into the spinel ferrite system resulted in an initial spike of the lattice parameter and crystallite size before proceeding to decrease as the rare-earth content continues to decrease. FESEM micrographs reveals agglomerated particles with considerable grain size distribution. The magnetic properties, especially the saturation magnetization, Ms, was found to decrease with each increase in La3+ substitution. The research findings revealed the critical influence of the La3+ substitution towards the overall structural and magnetic properties of the Mn-Zn ferrite samples. Â© 2018 Trans Tech Publications, Switzerland.